myAPEL : towards recognition of prior learning at Open University Malaysia - Kek , Lilian Siew Yick; Mansor Fadzil; Kaur , Harvinder (2011)
Working adults acquire valuable knowledge and skills throughout their lives and work experience. Learning occur through informal and non-formal means may be given due recognition and upon proper assessment, be used for advance standing or as an entrance qualification for access into higher education. Although the assessment of prior learning is common in developed countries, its practice in Malaysia is limited. Open University Malaysia (OUM) is a pioneer in the recognition of prior learning (RPL) efforts in the country. At present, its RPL practices include the (a) Flexible Entry System, a gateway for individuals to pursue higher education using lower academic entry qualifications and (b) Accreditation of Prior Experiential Learning (APEL), an avenue to assess and grant individuals with academic credits based on their experiential learning. This paper presents the RPL practices at OUM with a focus on APEL. It highlights the principles as well as processes of APEL within the institution. The description of the myAPEL system - an instrument specifically developed to capture and evaluate prior experiential learning based on specific learning outcomes - is included. The challenges involved in developing myAPEL and its benefits will also be discussed. This paper will be beneficial for institutions as well as learners who intend to capitalise on RPL. (Abstract by authors)